Biocompatible polydopamine-encapsulated gadolinium-loaded carbon nanotubes for MRI and color mapping guided photothermal dissection of tumor metastasis. (February 2017) - Wang, Sheng; Lin, Quanjun; Chen, Jiantao; Gao, Huile; Fu, Deliang; Shen, Shun
Abstract: Owing to the convenient and visual advantages, dye mapping agents are the most popular lymph tracing agents in the current clinic practices. However, limit tissue penetration always leads to hardly detect deeper lymph nodes (LNs), such as regional lymph nodes (RLNs). Therefore, exploring multimodal nanotheranostic agents for diagnosis and treatment of metastatic LNs are desired. In this study, polydopamine-encapsulated gadolinium-loaded multi-walled carbon nanotube (MWCNT-Gd@PDA) were strategically designed for dual-modality mapping guided photothermal therapy (PTT) by positive signal of magnetic resonance imaging (MRI) as well as deep black of the nanomaterials providing visual information. PDA, with excellent biocompatibility and biodegradability, can be easily deposited on many kinds of inorganic and organic materials to prepare functional materials. In order to prevent gadolinium ion escaping from the MWCNT, PDA shell was coated on the surface of MWCNT-Gd. Thus, the prepared MWCNT-Gd@PDA nanomaterials were lack of inherent biological toxicity. More importantly, under the guidance of dual-modality mapping, we demonstrated that primary tumors and RLNs could be simultaneously and effectively ablated by near-infrared irradiation to acquire the radical photothermal dissection. The results showed that our nanosystem possessed the precise spatial-temporal selectivity in comparison with conventional surgery and T2 -MRI guided PTT. Graphical abstract: